The photoactivated antifungal activity and possible mode of action of sodium pheophorbide a on Diaporthe mahothocarpus causing leaf spot blight in Camellia oleifera - Shi, Xu-Long; Yang, Jing; Zhang, Yu; Qin, Piao; Zhou, He-Ying; Chen, Yun-Ze (Frontiers in Microbiology, 2024)
Sodium pheophorbide a (SPA) is a natural plant-derived photosensitizer, with high photoactivated antifungal activity against some phytopathogenic fungi. However, its fungicidal effect on Diaporthe mahothocarpus, a novel pathogen that causes Camellia oleifera leaf spot blight, is unclear. In the present study, we found that SPA effectively inhibited the growth of D. mahothocarpus, with half-maximal effective concentrations to inhibit mycelial growth and spore germination of 1.059 and 2.287 mg/mL, respectively. After 1.0 mg/mL SPA treatment, the conductivity and malondialdehyde content of D. mahothocarpus were significantly increased. Scanning electron microscopy and transmission electron microscopy indicated that SPA significantly affected the morphology and ultrastructure of D. mahothocarpus hyphae, revealing that SPA can destroy the mycelial morphology and cell structure, especially the cell membrane of D. mahothocarpus. Furthermore, transcriptome analysis revealed that SPA significantly suppressed the expression of genes involved in morphology, cell membrane permeability, and oxidative stress. Then, we also found that SPA significantly promoted the accumulation of reactive oxygen species (ROS) in of D. mahothocarpus, while it decreased the content of reduced glutathione, inhibited the enzyme activities of superoxide dismutase and catalase, and exacerbated DNA damage. Annexin V-FITC/PI staining also confirmed that 1.0 mg/mL SPA could significantly induce apoptosis and necrosis. Generally, SPA can induce ROS-mediated oxidative stress and cell death, thus destroying the cell membrane and hyphal morphology, and ultimately inhibiting mycelial growth, which indicates that SPA has multiple modes of action, providing a scientific basis for the use of SPA as an alternative plant-derived photoactivated fungicide against C. oleifera leaf spot blight.